Trace metals concentrations in mangrove sediments of Sepetiba Bay (Rio de Janeiro, Brazil): microwave assisted digestion with nitric acid and aqua regia. - SOUZA, P. S. A. de (2012)
Mangrove sediments have a great capacity to accumulate trace metals that can be remobilized thus contaminating the water and biota. Concentrations of trace metals (Cu, Ni, Pb and Zn) in mangrove sediment samples from Sepetiba Bay (Brazil) determined using two different protocols were compared, in order to give support for the establishment of a future legislation of environmental assessment of sediment quality in Brazil. Surface sediment samples were collected in three mangrove forests of Sepetiba Bay and were analyzed to determine pH, Eh, salinity, and the percentages of sand, silt, clay, total organic carbon (TOC), total N and total P. Concentrations of Cu, Ni, Pb and Zn were determined using two microwave acid digestion protocols, with two different agents: nitric acid (HNO3) and aqua regia (HCl/HNO3). Results showed that the choice of the digestion method to use in the evaluation of environmental contamination and monitoring of trace metals in sediments should be made carefully, taking into account their physical and chemical characteristics in order to avoid misclassification of environmental impacts.